2008
DOI: 10.1007/s10457-008-9109-6
|View full text |Cite
|
Sign up to set email alerts
|

Traditional agroforestry systems as tools for conservation of genetic resources of Milicia excelsa Welw. C.C. Berg in Benin

Abstract: The potential contribution of agroforestry systems to the management and genetic resources conservation in iroko (Milicia excelsa), an important and valuable timber tree species in sub-Saharan Africa, is addressed in this paper. The structure and dynamics of traditional agroforestry systems and the ecological structure of Milicia excelsa populations in farmlands were studied through a survey carried out in 100 farmlands covering the natural range of iroko in Benin. Forty-five species belonging to 24 plant fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…This study is consistent with Atta-krah et al (2004), Acharya (2006), and Ouinsavi and Sokpon (2008), where traditional agroforestry practices support biodiversity through in situ conservation of tree species on farms and the choice of integrated tree species in the farming systems is guided by many reasons peculiar to farmers. For the majority of respondents surveyed, the selection criteria of tree species in the system were dependent on cash income as output.…”
Section: Tree Species Diversitysupporting
confidence: 92%
“…This study is consistent with Atta-krah et al (2004), Acharya (2006), and Ouinsavi and Sokpon (2008), where traditional agroforestry practices support biodiversity through in situ conservation of tree species on farms and the choice of integrated tree species in the farming systems is guided by many reasons peculiar to farmers. For the majority of respondents surveyed, the selection criteria of tree species in the system were dependent on cash income as output.…”
Section: Tree Species Diversitysupporting
confidence: 92%
“…Many authors have shown that traditional agroforestry practices contribute to the conservation of biodiversity through in situ conservation of tree species on farms, reduction of pressure on remnant forests, and the provision of suitable habitat for a number of plant and animal species on farmland (Atta-Krah et al 2004;Ouinsavi et al 2005;Acharya 2006, McNeely andSchroth 2006). Trees in these systems provide shade, shelter, energy, food, fodder and many other goods and services that enable the farmstead to prosper (Leakey and Tchoundjeu 2001;McNeely and Schroth 2006;Oke and Odebiyi 2007;Djossa et al 2008;Ouinsavi and Sokpon 2008). Wild fruits supplement the daily diet, substitute for exotic fruits, gain importance during periods of food shortage and are important sources of income for people through commercialization (Styger et al 1999;Teklehaimanot 2004;Djossa et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The plant also provides excellent fuel wood, premium quality timber, good fodder and green manure and compost (Anonymous 1992). Therefore, the tree species possess a great potential to be employed as a tool for traditional agroforestry systems and social and community forestry (Ouinsavi and Sokpon 2008) by conservation of germplasm through in vitro techniques.…”
Section: Introductionmentioning
confidence: 99%